Ilirizam i tumačenje snova: Gundulići Vlaha Bukovca - Jukić, Tatjana (Wydawnictwo Naukowe UAM, 2012)
Given the prominent position in the Croatian cultural imagination of Vlaho Bukovac’s 1895 painting of the Illyrian Movement, this article argues that the later accounts of early to mid- 19th-century Illyrian politics and literature remain contaminated, and structurally so, by Bukovac’s treatment of the visual. This visual contaminant then points to more general political and cultural practices in Austria-Hungary at the time, including psychoanalysis, not least where psychoanalysis addresses the scope of image and the phantasmatic. Analyzing three paintings where Bukovac takes up the subject of literature cum the phantasmatic alongside Freud’s 1908 study of „Der Dichter und das Phantasieren”, I propose that in both literature serves to indicate the political logic of metonymy or the metonymic logic of the political; furthermore, I show that Freud, unlike Bukovac, fails to sustain this logic precisely in places where he sets out to classify wishes.
Illyrian movement and the interpretation of dreams: Ivan Gundulić in the paintings of Vlaho Bukovac
Keywords: Illyrian movement; Psychoanalysis; Metonymy; Painting; Literature